The option of seeing: A comparative study between Islamic law and jurisprudence - Alaa Saad Mohammed; Ahmed Oday Hatem (International Journal of Law Research and Studies, 2025)
A person may face deception or unfair exploitation when hastily making a purchase, only to later discover they have fallen victim to fraud or deceit. They might rush into a transaction and then realize that the purchased item does not meet their needs or contains hidden defects. Similarly, an individual may sell something of personal value and later regret the sale. Some people lack sufficient experience in buying and selling, especially in complex commercial transactions, and may struggle to assess the qualities of a product due to the intricacies of modern goods. All these situations can lead to harm, regret, disputes among individuals, and instability in financial transactions. To address these issues, Islamic Sharia has wisely established the concept of "Khiyarat" (options) as a compassionate provision for contracting parties, aiming to protect the vulnerable party from unfair exploitation, deceit, or other defects. It grants the affected party the right to unilaterally rescind the contract. Similarly, secular laws seek to protect the weaker party in a contract by providing them with privileges that allow them to understand the subject matter of the contract without being disadvantaged. Among these privileges are "options," which grant their holder the right to either affirm or rescind the contract. Thus, the contract remains non-binding as long as the option period lasts, and the option holder may annul it without the consent of the other party.
Keywords: Vision; Secular Laws; Islamic Sharia; Option (Khiyar)